THE LOW-FREQUENCY SEISMIC SIGNAL FOREGOING A MAIN SHOCK AS A SIGN OF THE LAST STAGE OF EARTHQUAKE PREPARATION OR PRELIMINARY RUPTURE - Sassorova E.V.; Levin B.W. (My University, 2001)
The existance of low-frequency foregoing signals (LFFS) just before the main shock was described by Ihmle and Jordan (1991, 1993, 1994), Brevdo (1998), Levin and Sassorova (1994, 1995, 2000), Umeda (1999). The LFFS may be considered as a local sign of the last stage of the earthquake preparation or as a signal of the preliminary rupture process which preceded the main shock. These signals have a period from 3 to 200 s and forecast time before P-wave arrival in area from 5s to 1.5 hours. The LFFS were detected only for the events with epicenter distance no more than 1000 km. The LFFS parameters depend on the regional characteristics (the oscillator size, features of the environment, structure of the Earth crust). The LFFS properties connected with the same region, such as a period, foregoing time duration, signal structure vary insignificantly. The classification of the foregoing signals was proposed and the connection between the signal type, and the event localization was noted. It was shown that faint seismic signals radiated from an earthquake source and acoustic signals preceded a rupture in laboratory experiments can be written by common empirical relationship (the dependence of the period of radiated waves on the size of oscillation zone). The dispersion law for the signal emitted by the destruction source area is suggested, based on the laboratory experiments and field observations.
Keywords: Low-frequency foregoing signals; Earthquake